Adolescent motherhood and secondary schooling in Chile - Diana I. Kruger; Matias E. Berthelon; Rodrigo Navia (Institute for the Study of Labor (IZA), 2009)
We analyze the determinants of adolescent motherhood and its subsequent effect on high school attendance and completion in Chile. Using eight rounds of household surveys, we find that adolescents who were born to teen mothers, those that live in poor households and in single-mother families, are more likely to have children, while access to full-time high schools reduces the likelihood of motherhood. We then estimate the effect of adolescent motherhood on the probability of high school attendance and completion. Using an instrumental variables approach to control for possible endogeneity between teen pregnancy and schooling, we find that being a mother reduces the probability of high school attendance and completion by 24 to 37 percent, making it the most important determinant of high school desertion, which implies that policies aimed at reducing early childbearing will have immediate, important effects on their school attainments.
Keywords: J13; O12; O15; 330; Adolescent motherhood; high school completion; high school desertion; Chile; Jugendliche; Mütter; Allgemeinbildende Schule; Bildungsverhalten; Bildungsabschluss; Chile